MULTIMODAL CHARACTERISTICS OF WOMEN'S LANGUAGE ON INSTAGRAM: A DISCOURSE ANALYSIS OF DIGITAL IDENTITY AND ENGAGEMENT STRATEGIES (Scientific journal of the Fergana State University, 2025)
This study analyzes women’s language use on Instagram through textual, visual, and interactive modalities with the aim of understanding construction of identity and engagement with the audience. It employs a multimodal discourse analysis approach to 200 Instagram posts collected from influencers, activists, and professionals. The results show that women enhance their relatability and interaction with others through personal narratives, hashtags, and emoji’s which all markers of expressiveness are. In terms of self-representation, color schemes and body language together with curated visuals is important. Furthermore, self-generated and action inviting utterances elicit and build a participatory culture. This research sheds light the phenomenon of interaction online from the point of view of semiotics as well as draws attention to self and brand promotion and advocacy on the photo sharing website Instagram. This aids in the understanding of the intersection of digital discourse, gendered communication, and social media linguistics.